Fresh and Mechanical Properties of Limestone Calcined Clay Cement (LC3) using Local Clay with Clinker Content below 50% - Mihardja, Edwin; Antoni, Antoni; Riady, Elbert G.; Suhendro, Samuel V.; Susanto, Tri E.; Akbar, Rizky T.; Anuraga, Bangkit Tegar T.; Hardjito, Djwantoro (Institute of Research and Community Outreach - Petra Christian University, 2026)
This study examined the performance of limestone calcined clay cement (LC3) produced with Indonesian clays containing low–medium kaolinite (20–30%) and clinker contents below 50%. Material characterization was carried out using XRF, XRD, and particle size analysis, followed by evaluation of fresh and mechanical properties. LC3 mixtures incorporating local clays exhibited good workability and required less superplasticizer than metakaolin-based controls, indicating favourable fresh behaviour despite reduced clinker content. A notable strength reduction was observed when clinker content dropped below 35%, reflecting insufficient portlandite required for pozzolanic reactions. The addition or substitution of Ca(OH)₂ did not improve strength and hindered calcined clay reactivity due to elevated pH level (12.5–13.5). Microstructural analysis confirmed that mixtures with higher kaolinite and clinker contents produced denser hydration products. The results demonstrated that Indonesian clays are suitable for LC3 development, with promising fresh properties and microstructural behaviour supporting further optimization and future durability studies.